Evaluation of Medial Open-Wedge High Tibial Osteotomy Results - Özgür Erdoğan; Hakan Serhat Yanık (Southern Clinics of Istanbul Eurasia, 2019)
INTRODUCTION[|]There are several studies on medial open-wedge tibial osteotomy, but there is still some debate about the acceptable amount of preoperative flexion contracture degree. Also, clinical effects of alteration of the tibial slope after the procedure are not clear. This study aimed to investigate the mid-term the clinical and radiological findings and complications of medial open-wedge tibial osteotomy.[¤]METHODS[|]A total of 44 knees of 42 patients were retrospectively investigated between January 2001 and February 2012. Tibial sagittal slope, mechanical tibiofemoral angle (mTFA), mechanical lateral distal femoral angle (mLDFA), and medial proximal tibia angle (MPTA) were measured both preoperatively and postoperatively. The mean follow-up period was 92+-7 (range 70–113) months. In four (10%) patients, 10 degrees of flexion contracture was present preoperatively. The clinical outcome was evaluated with the Hospital for Special Surgery (HSS) Knee Score, Oxford Knee Score (OKS), and Knee Outcome Survey-Activities of Daily Living Scale (KOS-ADLS).[¤]RESULTS[|]The mean age of the participants was 45.7+-18.3 (range 17–84) years. There were 34 (81%) females and 8 (19%) males. The mean knee range of motion increased from 120+-11 to 130+-9 degrees, postoperatively. The HSS scores improved to excellent in 29 (69%), good in 9 (21%), and moderate in 4 (10%). The ADLS and Oxford scores improved two-fold.[¤]DISCUSSION AND CONCLUSION[|]In conclusion, further studies are needed to understand the relationship between flexion contracture and tibial sagittal slope. Therefore, in selected patients, flexion contracture may not be a restraint for osteotomy, especially if the slope increase is prevented.[¤]